2000
DOI: 10.1101/lm.7.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Glutamate Release by l-Fucose Changes Effects of Glutamate Receptor Antagonists on Long-Term Potentiation in the Rat Hippocampus

Abstract: In previous studies L-fucose has been shown to facilitate long-term memory formation and to enhance and prolong long-term potentiation (LTP). To search for possible presynaptic or postsynaptic mechanisms that are affected by L-fucose, we examined the effect of L-fucose on (1) inhibition of LTP induction via glutamate receptors by antagonists, (2) paired-pulse facilitation, and (3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…There are several articles describing some mechanisms that may be partially responsible for the effects of 2´-FL or Fuc on synaptic function [18, 34]. Injected L-fucose may have an influence on glutamate release at the hippocampal CA3-CA1 synapse [35]. Moreover, glycosylation of proteins during a critical time window following HFS of hippocampal slices is necessary for the adequate induction as well as maintenance of the evoked LTP [36], demonstrating the importance of Fuc residues in the frame of adequate neuronal processing.…”
Section: Discussionmentioning
confidence: 99%
“…There are several articles describing some mechanisms that may be partially responsible for the effects of 2´-FL or Fuc on synaptic function [18, 34]. Injected L-fucose may have an influence on glutamate release at the hippocampal CA3-CA1 synapse [35]. Moreover, glycosylation of proteins during a critical time window following HFS of hippocampal slices is necessary for the adequate induction as well as maintenance of the evoked LTP [36], demonstrating the importance of Fuc residues in the frame of adequate neuronal processing.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the epitope Fucα(1-2)Gal has been revealed as a key regulator of neurite outgrowth and synapse formation and maintenance [42,44]. Furthermore, it has been reported that L-fucose increased glutamate release and interfered with competitive glutamate receptor antagonists when applied to hippocampal slices [40].…”
Section: '-Fl Effects On Expression Of Selected Neural Function Markersmentioning
confidence: 98%
“…Among other mechanisms [17,39], injected L-fucose may have an influence on glutamate release at the hippocampal CA3-CA1 synapse [40]. In addition, it has been reported that glycosylation of proteins during a critical time window following HFS of hippocampal slices is…”
Section: '-Fl Effects On Ltp Evoked At Hippocampal Synapsesmentioning
confidence: 99%
“…These suggestions are supported for 2’FL by our observations with video recordings showing decreased frequency, reduction of amplitude and velocity of colonic motor contractions. Since the effects of fucosylated oligosaccharides clearly occur through interactions, directly or indirectly with the ENS, we speculate that they could well also be exerting a positive effect on the brain via the vagus nerve [45,46] in supporting cognition and memory [47,48]. …”
Section: Discussionmentioning
confidence: 99%